Chromatin Remodeling of Colorectal Cancer Liver Metastasis is Mediated by an HGF‐PU.1‐DPP4 Axis. Issue 19 (10th August 2021) - Wang, Lihua; Wang, Ergang; Prado Balcazar, Jorge; Wu, Zhenzhen; Xiang, Kun; Wang, Yi; Huang, Qiang; Negrete, Marcos; Chen, Kai‐Yuan; Li, Wei; Fu, Yujie; Dohlman, Anders; et al.
Abstract: Colorectal cancer (CRC) metastasizes mainly to the liver, which accounts for the majority of CRC‐related deaths. Here it is shown that metastatic cells undergo specific chromatin remodeling in the liver. Hepatic growth factor (HGF) induces phosphorylation of PU.1, a pioneer factor, which in turn binds and opens chromatin regions of downstream effector genes. PU.1 increases histone acetylation at the DPP4 locus. Precise epigenetic silencing by CRISPR/dCas9 KRAB or CRISPR/dCas9 HDAC revealed that individual PU.1‐remodeled regulatory elements collectively modulate DPP4 expression and liver metastasis growth. Genetic silencing or pharmacological inhibition of each factor along this chromatin remodeling axis strongly suppressed liver metastasis. Therefore, microenvironment‐induced epimutation is an important mechanism for metastatic tumor cells to grow in their new niche. This study presents a potential strategy to target chromatin remodeling in metastatic cancer and the promise of repurposing drugs to treat metastasis. Abstract : Metastasis of colorectal cancer to the liver is a leading cause of cancer‐related death. This work shows that metastatic colorectal cancer cells undergo chromatin remodeling in the liver via an HGF‐PU.1‐DPP4 axis. Pharmacological or genetic inhibition of this remodeling axis can suppress liver metastasis and prolong survival.